The Application Of Technology Acceptance Model (TAM) In Verifying “Draiv” Usage Intention - junita, Junita Safitri (IAIN Langsa, 2024)
This research is aim to verify the affecting Factor of Attitude Platform Usage , contemporary investigating the dominant factor that determines The Platform Usage Intention. Hypothesis testing were conducted using Quantitative method. The Research was conducted using an online survey approach. The Sample comprised 218 customers. The data collected were analyzed using PLS (Partial Least Square) Structural Equation Model. This Paper attempted to examine the customer response about the Kind of Courier Service Business that provide an organized system which operate in Indonesia by using TAM. The Findings indicated that technology usage was predicted by Behavioral Intention, while Behavioral Intention influenced by Attitude and Perceived Usefulness, when attitude and perceived usefulness were predicted by Perceived ease of use. Perceived Ease of Use Equals to Perceived Usefulness. While Perceived usefulness failed to affect attitude toward technology usage